SOURSOP POTENCY AS THE SUBSTRATE IN NATA DE ANONNA PRODUCTION - Indah Juwita Sari; Handa Sukarya; Hesty Mustikawati; Kharisma Putri Budi Utami; Novi Safitri; Dwi Ratnasari (University of Sultan Ageng Tirtayasa, 2019)
Nata is a functional food that has a healthy effect when consumed because it contains vitamin C which is beneficial to the body. Nata derived from soursop fruit, we know as nata de anonna, which is produced from the bacterial activity of Acetobacter xylinum. This study aims to determine the potential of soursop fruit skin as a substrate for making nata de anonna. Research shows that the yield nata produced from soursop fruit and soursop skin and soursop meat are (1.5 cm, 1 cm and 0.8 cm). This research can be concluded that the hump and soursop skin which become waste are part of the soursop fruit can be used as the substrate of nata de anonna.